The Importance of Higher Education in the Era of the National Capital City(IKN): Pentingnya Pendidikan Tinggi Di Era Ibu Kota Negara (IKN) - Yeni Rahmawati; Rabi’ah Al-Adawiyah; Restuti Retno Ningrum; Andi M Juliansyah Abdul Aziz; Emila Wardani; Ahmad Irawan Nugraha; Yaskur Falah Bakri (Wadah Inovasi Indonesia, 2023)
On July 22, 2024 to. 22 September 2024, we have carried out the activities of the Real Work Lecture (KKN) program at SMA Negeri 2 Samboja. The KKN program aims to assist students' academic and non-academic activities and help complete the lack of facilities and infrastructure at SMA Negeri 2 Samboja. These programs include competition activities (collab) with Osis and students in commemoration of the Indonesian Independence Day on August 17, which was held on September 02, 2024 to September 04, 2024, namely the Fashion Show Competition with the theme “Historic Heroes”. Furthermore, the implementation of the seminar work program was carried out with the target of class XII SMA Negeri 2 Samboja with the theme “The Importance of Higher Education in the Era of the New Capital City (IKN)”. As well as the school maintenance and cleanliness work program, namely the making of garbage cans. We can carry out these activities well and can be accepted by all residents of SMA Negeri 2 Samboja.